Multidirectional insights into the phytochemical, biological, and multivariate analysis of the famine food plant (Calligonum polygonoides L).: A novel source of bioactive phytocompounds. (November 2020) - Pervaiz, Irfan; Saleem, Hammad; Sarfraz, Muhammad; Imran Tousif, Muhammad; Khurshid, Umair; Ahmad, Saeed; Zengin, Gokhan; Ibrahime Sinan, Kouadio; Locatelli, Marcello; Mahomoodally, Fawzi M.; Asnawi Zainal Abidin, Syafiq; Ahemad, Nafees
Graphical abstract: Highlights: Phytochemical and biological profiling of different solvent extracts of Calligonum polygonoides were investigated. UHPLC-MS and HPLC-PDA analysis revealed different flavonoid, phenolic, alkaloid, and terpenoid derivatives. All the extracts presented varied antioxidant and enzyme inhibition potential. Univariate analysis showed that chloroform and n -hexane were suitable solvent to recover biomolecules with highest biological activities. Abstract: Calligonum polygonoides L. also known as famine food plant, is normally consumed in times of food scarcity in India and Pakistan and also used traditionally in the management of common diseases. The present design aims to provide an insight into the medicinal potential of four solvent extracts of C. polygonoides via an assessment of its phytochemical profile, antioxidant and enzyme inhibitory potential. Phytochemical composition was estimated by deducing total bioactive constituents, UHPLC-MS secondary metabolites profile, and HPLC phenolic quantification. Antioxidant potential was determined via six methods (radical scavenging (DPPH and ABTS), reducing power (FRAP and CUPRAC), phosphomolybdenum total antioxidant capacity and metal chelation activity). Enzyme inhibitory potential was assessed against clinical enzymes (acetylcholinesterase -AChE, butyrylcholinesterase -BChE, tyrosinase, and α-amylase). The highest amounts of phenolic contents were found in chloroform extract (76.59 mg GAE/g extract) which may be attributed to its higher radical scavenging, reducing power and tyrosinase inhibition potential. The n -butanol extract containing the maximum amount of flavonoids (55.84 mg RE/g extract) exhibited highest metal chelating capacity. Similarly, the n -hexane extract was found to be most active against AChE (4.65 mg GALAE/g extract), BChE (6.59 mg GALAE/g extract), and α-amylase (0.70 mmol ACAE/g extract) enzymes. Secondary metabolite assessment of the crude methanol extract as determined by UHPLC-MS analysis revealed the presence of 24 (negative ionization mode) and 15 (positive ionization mode) secondary metabolites, with most of them belonging to phenolic, flavonoids, terpene, and alkaloid groups. Moreover, gallic acid and naringenin were the main phenolics quantified by HPLC-PDA analysis in all the tested extracts (except n -butanol extract). PCA statistical analysis was also conducted to establish any possible relationship amongst bioactive contents and biological activities. Overall, the C. polygonoides extracts could be further considered to isolate bioactive enzyme inhibitory and antioxidant natural phytocompounds.